Application Of Tooth Coronal Index (TCI) Benindra Method In Estimating Biological Age at Sultan Agung Dental Hospital Semarang - Niluh Ringga Woroprobosari; Dinda Vinca Rosa; Adisty Restu Poetri (Denta Journal Kedokteran Gigi, 2023)
Background: Age estimation through dental approaches is often an option for establishing identity in forensic cases. Age estimation can clarify statements of death, legal and civil matters. One way to identify victims is using periapical radiographs. The use of periapical radiographs in age estimation requires certain methods, one of them is using TCI (Tooth Coronal Index) Benindra method modified from Drusini's TCI method. Tooth age assessment using the Benindra TCI method was based on pulp chamber height measurements. Objective: The research was carried out to clarify the possibility of the TCI Benindra method application in estimating biological age in the Sultan Agung Dental Hospital Semarang population. Methods: This study used 23 periapical radiographs from 7 male and 16 female patients of Sultan Agung Dental Hospital Semarang. The age estimation by Benindra TCI method was performed at the age of 9-21 years towards the mandibular premolar tooth. Tooth age assessment was based on measuring the pulp chamber height using the TCI formula. Results of TCI measurements were entered into the prediction age formula to determine the patient’s biological age. Results: The difference between the average estimated biological age using the Benindra method and the average chronological age was up to 0,46 years in the 9-21 years age group. 7 data were underestimated, 6 data were overestimated, and 10 data were accurately estimated. Conclusion: The application of the Benindra TCI method showed precise results for dental patients in Semarang, so that could be used to estimate the biological age of the general population.